1999
DOI: 10.1021/jo990636c
|View full text |Cite
|
Sign up to set email alerts
|

AM1-SM2 Calculations Model the Redox Potential of Nitroxyl Radicals Such as TEMPO

Abstract: Nitroxyl radicals can be oxidized to N-oxo ammonium salts that are themselves useful oxidants for primary and secondary alcohols. Several computational methods were investigated in order to predict the redox potential of nitroxyl radicals and to better understand the behavior of different nitroxides as catalysts for alcohol oxidation. The difference in calculated heats of formation for N-oxo ammonium ions and nitroxyl radicals using AM1 did not lead to a useful correlation with experimental redox potential as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…However, the failure of the reaction in the presence of TEMPO can be explained; the latter is easily oxidized itself by the applied oxidant PhI(OAc) 2 (Table 2). Moreover, if TEMPO was taken in two-fold excess over the oxidant, the entire oxidant was consumed by the side reaction of TEMPO oxidation, which is easily oxidized to about 0 V [60,61], but not by the oxidation of more difficultly oxidized palladacycles. It is known that oxammonium salts are effective oxidant species derived from TEMPO [79].…”
Section: Methodsmentioning
confidence: 99%
“…However, the failure of the reaction in the presence of TEMPO can be explained; the latter is easily oxidized itself by the applied oxidant PhI(OAc) 2 (Table 2). Moreover, if TEMPO was taken in two-fold excess over the oxidant, the entire oxidant was consumed by the side reaction of TEMPO oxidation, which is easily oxidized to about 0 V [60,61], but not by the oxidation of more difficultly oxidized palladacycles. It is known that oxammonium salts are effective oxidant species derived from TEMPO [79].…”
Section: Methodsmentioning
confidence: 99%
“…However, none of these nitroxides outperforms TEMPO and its derivatives. Rychnovsky et al 18 measured the redox potentials of oxammonium salts formed from cyclic nitroxides, using cyclic voltammetry, whereas Suemmermann and Deffner 109 measured those of acyclic nitroxides. There are also examples of oxidations carried out with oxammonium salts formed electrochemically.…”
Section: Nitroxide Backgroundmentioning
confidence: 99%
“…Ali and Wazeer 178 and others 179 have shown that oxammonium compounds are intermediates in the preparation of nitrones by the oxidation of the corresponding hydroxylamines. Rychnovsky et al 18 showed that TEMPO can be oxidized to the corresponding oxammonium and reduced to the corresponding hydroxylamine anion electrochemically. This is the common pattern observed with bisneopentyl nitroxides in which the corresponding oxammonium cannot undergo tautomerization.…”
Section: Proposed A-hydrogen Nitroxide Decomposition Mechanismmentioning
confidence: 99%
See 2 more Smart Citations